2021
DOI: 10.3390/biology10090827
|View full text |Cite
|
Sign up to set email alerts
|

Plant Resources Utilization among Different Ethnic Groups of Ladakh in Trans-Himalayan Region

Abstract: The nomadic pastoral indigenous communities of the Ladakhi people share roots with Tibetan culture in terms of food, clothing, religion, festivals, and habits, and rely widely on plant resources for survival and livelihood. This survey was conducted during 2019–2021 to document the indigenous knowledge about plant resources of the Balti, Beda, and Brokpa communities of the Ladakh region, trans-Himalayas. Open- and close-ended semi-structured interviews (N = 184) and group discussions (N = 17) were used to coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 76 publications
(87 reference statements)
4
49
0
Order By: Relevance
“…Various ethno-veterinary studies produce similar findings ( 28 , 34 , 36 ). Many researchers have also identified the Asteraceae, Brassicaceae, and Lamiaceae families as the most representative of the Himalayan regions ( 16 , 26 – 29 , 32 , 33 , 37 ), demonstrating the family's great adaptability in many climates and geographies ( 38 ). This study found unequal family distribution patterns with 44 monotypic families, which is consistent with prior ethno-veterinary studies from various Himalayan locations ( 17 , 34 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Various ethno-veterinary studies produce similar findings ( 28 , 34 , 36 ). Many researchers have also identified the Asteraceae, Brassicaceae, and Lamiaceae families as the most representative of the Himalayan regions ( 16 , 26 – 29 , 32 , 33 , 37 ), demonstrating the family's great adaptability in many climates and geographies ( 38 ). This study found unequal family distribution patterns with 44 monotypic families, which is consistent with prior ethno-veterinary studies from various Himalayan locations ( 17 , 34 , 39 ).…”
Section: Resultsmentioning
confidence: 99%
“…Principal component analysis (PCA) ( 16 ) was used to determine hypothetical variables (components) that explain as much of the variance in our multidimensional data as possible in associational analyses between different ethnic groups and plant compositions. We calculated the singular value decomposition of the (centered and possibly scaled) data matrix using a matrix of plant species presence/absence in each of the three regions analyzed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Taxonomic identification was carried out by using the online database “Integrated Taxonomic Information System” ( ) (accessed on 17 August 2021) and using the regional literature [ 26 , 31 ]. We have also compared the recorded data with the previous ethnobiological literature carried out in the nearby regions, particularly surrounding the Himalayan regions [ 10 , 26 , 32 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. The conservation assessment of documented fauna species was done as per the International Union for Conservation of Nature (IUCN, 2019) Red List ( ) (accessed on 17 August 2021) and used the regional literature [ 31 ].…”
Section: Methodsmentioning
confidence: 99%